Validation of the Oswestry Risk of Knee Arthroplasty Index (ORKA-1) for Patients Undergoing Autologous Chondrocyte Implantation. (October 2020) - Ackermann, Jakob; Barbieri Mestriner, Alexandre; Arango, Dillon; Ogura, Takahiro; Gomoll, Andreas H.
Objective: The purpose of this study was first to externally validate the Oswestry Risk of Knee Arthroplasty index (ORKA-1) by applying it to an autologous chondrocyte implantation (ACI) patient cohort in the United States with a broader definition of failure than only arthroplasty, and second, to determine predictive factors for the risk of ACI failure as defined by the senior author. Design: A total of 171 patients that underwent ACI were included to validate the ORKA-1 as all factors needed for calculation and outcomes were recorded. For Cox regression analysis, 154 patients were included as they completed preoperative Knee Injury and Osteoarthritis Outcome Score (KOOS), Tegner, Lysholm, International Knee Documentation Committee (IKDC), and 12-item Shor Form (SF-12) scores. Patient- and lesion-associated parameters were recorded for each patient. Results: At final follow-up (maximum of 10 years post-ACI), a total of 27 patients (15.8%) were considered a failure by senior author's definition. With ACI failure as endpoint, the mean survival was 7.96 years in risk group 1 and 5.4 years in risk group 5. Cox regression analysis identified preoperative KOOS Sport/Recreation as the only significant predictive factor for ACI failure ( P = 0.007). Conclusion: The ORKA-1 is a helpful tool for surgeons to estimate an individual patient's likelihood of ACI survival. Further studies with larger patient cohorts as well as a consensus definition of failure are needed to further refine predictors of ACI failure.